The Effect of Thermochemical Sulphate Reduction on the Carbon Isotope Ratio of Individual Light Hydrocarbons Associated With Natural Gas - Hu, Guoyi; Guo, Jinhao; Tian, Lianjie; Wu, Xiaoqi; Su, Jin; Li, Zhisheng; Fang, Chenchen (Frontiers in Earth Science, 2022)
To understand the effect of thermochemical sulphate reduction (TSR) on the stable carbon isotopes of light hydrocarbons (LHs) associated with natural gas, 15 gases with varying H2S content from Ordovician reservoir of the Tazhong gas field (TZ-I) in Tarim Basin and Triassic Leikoupo reservoir of the Zhongba gas field (ZB) in Sichuan Basin were collected. Based on the data from molecular components and stable carbon isotope ratios of the C1-C4 alongside the individual LHs (C6-C7) in these gases, the origin of natural gas and the effect of TSR on the stable carbon isotope ratio of individual LHs were studied. The δ13C in ethane (<−28‰), LHs (<−26‰) and the composition distribution characteristic of C6-C7 indicated that the gases were oil-associated gases. Moreover, the gas sourness index, defined as H2S/(H2S+∑Cn) demonstrated that the gases from the TZ-I and ZB gas fields were in the early liquid-hydrocarbon-involved and heavy-hydrocarbon-gas-dominated TSR stages, respectively. The comparison of stable carbon isotope ratios of the LHs between the two gas fields revealed that TSR exhibited a complex effect on the carbon isotope values of LHs, but only little effect on 2-methylpentane (2-MP) and 3-methylpentane (3-MP). The δ13C values of benzene (BEN) and toluene (TOL) were -28.3‰ and -29.4‰ in the TZ-I and -27.7‰ and -28.1‰ in the ZB gas field. The stable carbon isotope ratios of BEN and TOL in ZB gas field exhibited more enriched 13C than those in TZ-I gas field, likely driven by TSR. Meanwhile, cycloalkanes, such as methyl cyclopentane (MCP), cyclohexane (CH), and methylcyclohexane (MCH), enriched 13C with TSR process and displayed a greater trend than aromatic compounds, about 2‰. Therefore, the influence of TSR on the carbon isotopes of individual LHs should be considered while using the stable carbon isotope ratio of cycloalkanes, BEN, and TOL to identify the genetic type and source of marine natural gas, especially at the cross plot (δ13C = −24‰) of coal-derived gas and oil-associated gas.